The Povarov Reaction: A Versatile Method to Synthesize Tetrahydroquinolines, Quinolines and Julolidines - Ferreira de Paiva, Walysson; de Freitas Rego, Yuri; de Fátima, Ângelo; Fernandes, Sergio Antonio (Synthesis, 2022)
The multicomponent Povarov reaction represents a powerful approach for the construction of substances containing N-heterocyclic frameworks. By using the Povarov reaction, in addition to accessing tetrahydroquinolines, quinolines and julolidines in a single step, it is possible to form the following new bonds: two Csp3–Csp3 and one Csp3–Nsp3, two Csp2–Csp2 and one Csp2–Nsp2, and four Csp3–Csp3 and two Csp3–Nsp1, respectively. This short review discusses the main features of the Povarov reaction, including its mechanism, the reaction scope by employing different catalysts and substrates, as well as stereoselective versions.1 Introduction2 Mechanism of the Povarov Reaction3 Tetrahydroquinolines4 Quinolines5 Julolidines6 Concluding Remarks
Keywords: multicomponent reactions; N-heterocyclic compounds; reaction mechanism; catalysis